The Impacts of nearshore bathymetry and lunar tidal variation on sea turtle emergence in Miami -Dade Country, Florida - Benner, Faith Lindsey (Scholarly Repository, 2018)
Florida provides vital nesting grounds for three species of sea turtles; loggerheads (Caretta caretta), greens (Chelonia mydas), and leatherbacks (Dermochelys coriacea). This study sought to discern the impact of lunar tidal variation and nearshore bathymetry on emergence location and timing of these three sea turtles in Miami Dade County. Data, including date and GPS location, of 1,143 sea turtle emergencies in Miami Dade County were collected by sea turtle surveyors in the Miami Dade County Sea Turtle Conservation Program during the 2017 sea turtle nesting season. Three lunar factors were tested in relation to sea turtle emergence timing. No relationship existed between the percentage of the moon illuminated and the number of sea turtle emergencies on corresponding nights (p=0.766), nor was there a relationship between tidal range and the number of sea turtle emergencies on corresponding nights (p=0.481). The proportion of sea turtle emergencies occurring during spring or neap tides was also not significantly different (p=0.0131). Nearshore bathymetry was also correlated with sea turtle emergence density across the five beaches in Miami Dade County, using depth at 100m offshore as a proxy for coastal slope. Two beaches, Miami Beach (p=0.0002) and Key Biscayne (p=0.0007) showed a strong negative relationship between coastal slope and sea turtle emergence density. One beach, Golden Beach, showed only a marginally significant negative relationship between coastal slope and sea turtle emergence density (p=0.054). Two beaches, Fisher Island (p=0.486) and Haulover Beach (p=0.714) showed no relationship between coastal slope and sea turtle emergence density. Sea turtles nesting in Miami Dade County appear to do so independently of the time in the lunar cycle, and, on some beaches, prefer emerging in locations where the coastal slope is larger and more severe. This knowledge of where sea turtles prefer to emerge is useful in allocating conservation resources to ensure that those areas have the highest level of protection possible.